Baptist Political Theology - Kidd, Thomas S. (B&H Publishing Group, 2023)
Early Baptist leaders thought deeply about politics and church-state relations, and Baptists today continue to wield a vital influence in the public square. Baptist Political Theology surveys the historical development, core principles, enduring commitments, and contributions to current issues made by Baptists in politics.